Prevalence of depressive symptoms and associated factors among adolescents living with HIV/AIDS in South Western Uganda - Kemigisha, Elizabeth; Zanoni, Brian; Bruce, Katharine; Menjivar, Ricardo; Kadengye, Damazo; Atwine, Daniel; Rukundo, Godfrey Zari (AIDS Care, 2019)
Adolescents living with HIV (ALHIV) are prone to depression, which can have detrimental effects including disease progression, poor treatment adherence and mortality. We aimed to determine the prevalence of depressive symptoms and their associated factors among ALHIV in Uganda. We conducted a cross-sectional survey among ALHIV (10–19 years) attending urban and rural clinics in Mbarara, Uganda between March and May 2017. Presence of depressive symptoms was assessed using the Centre for Epidemiological Studies’ Depression scale. We interviewed 336 adolescents with a median age of 13 years, 62% of whom were female. A third (37%) had disclosed their HIV/AIDS status and 13% were sexually active. Overall, 154 (∼46%, [95% CI: 40.5– 51.2]) had depressive symptoms. On bivariate analysis, the odds of having depressive symptoms were higher among adolescents who were ≥ 15 years, had disclosed HIV status, traveled >30 min for routine care and had risky sexual practices. On multiple variable analysis, only travel time to the clinic of >30 min was independently associated with depressive symptoms (AOR = 1.6 [95% CI: 1.02–2.7]). With the high prevalence of depressive symptoms among ALHIV in Uganda, screening and prompt treatment of depression should be incorporated within their routine care.
Keywords: Adolescents; Depressive symptoms; HIV/AIDS; Uganda